Pengaruh Lingkungan Kerja dan Kompensasi terhadap Loyalitas Karyawan Hotel BW Luxury Jambi - Sonia Oktavianis; Youmil Abrian (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the results of interviews with HRD BW Luxury Hotel Jambi, it is stated that there are still employees who are often late for work every month. As many as 27% of employees have less than 1 year of service, indicating a high employee turnover rate. In addition, there is no compensation system provided to employees. The employee turnover rate also reached 13%, this became the focus of my research on the influence of work environment and compensation on employee loyalty at BW Luxury Hotel Jambi. Information collection was carried out through distributing questionnaires that had proven their validity and reliability to 90 respondents selected using the total sampling technique. This research is a quantitative descriptive study that uses the clausal associative method. Data analysis was carried out using multiple linear regression tests with the help of SPSS software. The results showed that: work environment variables were in the sufficient category with a percentage of 34.4%, compensation variables were categorised as sufficient with a percentage of 36.6%, and work environment variables were categorised as good with a percentage of 42.2%. The R Square value obtained is 0.325 with a sig level. 0.00 <0.05, then the effect of work environment variables and compensation variables on loyalty is 32.5% and the rest is influenced by other factors.